Pengaruh Perubahan Sisi Elektrode Sangkar Delta pada Nilai Resistans Satu Batang Pentanah - Harnoko Stephanus (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Grounding rod is more practical than grounding plate or grounding strip. Grounding resistance value must be set as small as possible. But, it is hard to approach the standard grounding resistance value. There are some methods used to reduce grounding resistance like paralleling ground rod, extending ground rod, or enlarging ground rod diameter. This paper explains the effect of side variation of delta cage electrode (dimension of delta length is 1 meter) on single ground rod resistance value. In this research, ground rod’s length and diameter are 1.5 meter and 10 millimeter, respectively. Ground rod is planted on the ground while the but is on land surface. Grounding resistance value of that single ground rod then is being compared with grounding resistance value of the combination of single ground rod and the delta cage electrode (dimension of delta side are 0.5 meter, 1 meter, and 1.5 meter). This research concludes that: (a) Delta cage electrode (its side are 0.5 meter, 1 meter, and 1.5 meter) with three edge rod length 1.5 meter (diameter 10 millimeter) can minimize grounding resistance value of single ground rod (length 1.5 meter, diameter 10 millimeter) by 29 ohm, 33 ohm, and 40 ohm. (b) Delta cage electrode (its side are 0.5 meter, 1 meter, and 1.5 meter) with six edge rod length 1.5 meter (diameter 10 millimeter) can minimize grounding resistance value of single ground rod (length 1.5 meter, diameter 10 millimeter) by 34 ohm, 37 ohm, and 43 ohm.